2020
DOI: 10.2174/1570159x18666200302125146
|View full text |Cite
|
Sign up to set email alerts
|

The e-Psychonauts’ ‘Spiced’ World; Assessment of the Synthetic Cannabinoids’ Information Available Online

Abstract: Background: A wide range of novel psychoactive substances (NPS) is regularly searched and discussed online by web-based drug enthusiasts (i.e. the e-psychonauts). Among NPS, the range of synthetic cannabinoids (SC; ‘Spice’) currently represents a challenge for governments and clinicians. Methods: Using a web crawler (i.e. the NPS.Finder®) the present study aimed at assessing psychonauts’ fora/platforms to better understand the online mentions of SC. Results: The open-web crawling/navigating software identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…The results presented here for the activity of the NPSfinder® web crawler showed the importance of the web as an essential source to understand and assess the NPS phenomenon ( 60 ). Indeed, previous research from our group ( 21 23 , 61 ) showed how the overall numbers of synthetic cathinones, opioids, benzodiazepines, and SCRAs identified online since the launch of NPSfinder® (November 2017) were higher than those reported to, and listed by, both the EMCDDA and the UNODC. Some 10/18 of the molecules here identified and commented online at the time of the pandemic were unknown/unreported NPSs ( 19 ), and this may highlight the potential of automated web crawlers to accurately describe the evolving drug scenarios.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The results presented here for the activity of the NPSfinder® web crawler showed the importance of the web as an essential source to understand and assess the NPS phenomenon ( 60 ). Indeed, previous research from our group ( 21 23 , 61 ) showed how the overall numbers of synthetic cathinones, opioids, benzodiazepines, and SCRAs identified online since the launch of NPSfinder® (November 2017) were higher than those reported to, and listed by, both the EMCDDA and the UNODC. Some 10/18 of the molecules here identified and commented online at the time of the pandemic were unknown/unreported NPSs ( 19 ), and this may highlight the potential of automated web crawlers to accurately describe the evolving drug scenarios.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, one could argue that of the 18 new NPSs identified here, only 10 were not in EMCDDA and UNODC databases at the time of the analysis, and hence only 10 were new. Conversely, as in previous articles ( 21 23 ), we thought that it was useful to provide the reader with comparison of current with existing data at the time of the analysis provided by reliable NPS databases such as the EMCDDA and UNODC. Although eight NPSs were already identified by these databases, they were discussed online by the psychonauts at the time of the pandemic, and hence they were grouped together with the “new” ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some users seemed to be cautious about using substances at home during the pandemic, for others (e.g., “psychonauts”; [ 43 , 44 , 47 , 107 , 108 ]), the confinement experience triggered the use of NPS and/or psychedelics to facilitate insight and mental exploration issues. Indeed, some r/DrugNerds and r/researchchemicals Redditors seemed to focus on a compulsive search for new molecules to be tried.…”
Section: Discussionmentioning
confidence: 99%
“…The illegal use of synthetic cannabinoids (SCs) has been growing exponentially [ 1 , 2 , 3 ]. These drugs represent one of the largest groups of new psychoactive substances (NPS), gaining significant importance in clinical and forensic toxicology.…”
Section: Introductionmentioning
confidence: 99%